Analysing University Students’ Coping Mechanisms for Academic Anxiety: A Structural Equation Modelling Approach - Iniya V; Padma S R; Karthikeyan C (Archives of Current Research International, 2025)
Aim: Globally, a major contributing factor to students’ poor performance is academic anxiety, which is fueled by psychological, emotional and social pressures. It results from a fear of being criticized by peers, parents or teachers. This study investigated the primary causes of students’ academic anxiety as well as the coping mechanisms they employ to deal with it. Place and Duration of Study: The study was conducted among final year undergraduate students (n=240) of Tamil Nadu Agricultural University, Coimbatore during 2024. Methodology: Data were subjected to descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM) method was employed to identify the most commonly used coping strategy by the university students in managing academic anxiety. Results: The study findings revealed that the academic factors were the most influential contributors to academic anxiety among students, which resulted in low academic performance, where only 13% of the total respondents had higher OGPA (Overall Grade Point Average). Problem-solving emerged as a statistically significant coping strategy (P = .038) adopted by students in response to academic anxiety. The model exhibited good fit (SRMR = 0.056; R² for coping strategy = 0.47), indicating substantial explanatory power. Conclusion: Recognizing academic pressures as key drivers of student anxiety is crucial for safeguarding educational outcomes. Equipping students with robust problem-solving skills emerges as an essential intervention to alleviate anxiety and encourage long-term academic success. This study offers practical implications for developing support programs for improving students’ mental well-being.